Popular juries in Argentina (1868-1874). The problem of democracy as the participation of the people in the government - Cucchi, Laura (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article analyzes some doctrinal and political disputes that took place over how the exercising of popular sovereignty should assume the construction of the Argentinian state. The focus is on the controversies brought about by the legislation of popular juries for the administration of justice. With those objectives, and from a perspective of political-intellectual history, the article approaches the forum of controversies that was constituted around academic production in the University of Buenos Aires and the legislative debates that took place in the National Congress. It also takes into consideration articles published in cultural and legal journals which articulated,fed and amplified the spread of those discussions. The main argument is that the dissidences that gave way to that form of popular sovereign exercise went back to the disputes over what the place of the people was in the government of the republic, and that its lack of implementation was linked to the triumph of a form of republican functioning which privileged popular demobilization as a means to secure political stability.